Social and ecological drivers of reproductive seasonality in geladas. (17th February 2018) - Tinsley Johnson, Elizabeth; Snyder-Mackler, Noah; Lu, Amy; Bergman, Thore J; Beehner, Jacinta C
Abstract: Many nonseasonally breeding mammals demonstrate some degree of synchrony in births, which is generally associated with ecological factors that mediate fecundity. However, disruptive social events, such as alpha male replacements, also have the potential to affect the timing of female reproduction. Here, we examined reproductive seasonality in a wild population of geladas ( Theropithecus gelada ) living at high altitudes in an afro-alpine ecosystem in Ethiopia. Using 9 years of demographic data (2006–2014), we determined that, while females gave birth year-round, a seasonal peak in births coincided with peak green grass availability (their staple food source). This post-rainy season "ecological peak" in births meant that estimated conceptions for these births occurred when temperatures were at their highest and mean female fecal glucocorticoid concentrations were at their lowest. In addition to this ecological birth peak, we also found a separate birth peak that occurred only for females in groups that had experienced a recent replacement of the dominant male (i.e., a takeover). Because new dominant males cause abortions in pregnant females and kill the infants of lactating females, takeovers effectively "reset" the reproductive cycles of females in the group. This "social birth peak" was distinct from the ecological peak and was associated with higher rates of cycling and conceptions overall and higher glucocorticoid levels immediately following a takeover as compared to females that did not experience a takeover. These data demonstrate that social factors (in this case, male takeovers) can contribute to population-level reproductive seasonality above and beyond group-level reproductive synchrony. Abstract : Waiting for the baby boom? For geladas, baby booms—or birth peaks—track not just the weather, but also recent social events. Although geladas can give birth year-round, we show that conceptions increase when temperatures are warm, resulting in a birth peak 6 months later. More surprisingly, we show that male takeovers—where the dominant male is replaced—effectively "reset" the reproductive cycles of affected females, creating a second, social, birth peak.